Model experimental investigation on staggered segmental tunnel linings considering the surrounding soil pressure - Mingyu Li; Jinghui Yang; Jian Chen; Gongbiao Yang; Longji Wu; Zhiyong Liu; Junwei Jin (Scientific Reports)
Abstract The surrounding soil pressure will significantly impact the existing tunnel lining. To study the deformation characteristics of the staggered segmental tunnel linings structure under this pressure, a model test device considering surrounding soil pressure effects is designed. This device simulates the impact of surrounding soil pressure on staggered lining using special prestressed springs. A bolt connected staggered lining model is also developed. Additionally, concentrated load F simulates loading conditions in some projects, applied to the lining structure. The reliability of test results is validated through numerical simulation. This study investigates segment displacement variations, including tunnel crown vertical displacement V d, ring and longitudinal joint dislocations CJ and LJ, and convergence deformation C. And the relationship between longitudinal joint dislocation and ring lining deformation. Based on these findings, relationships among vertical displacement, ring joint dislocations, vertical convergence, and longitudinal joint dislocation in the staggered segmental tunnel linings structure are established, offering valuable insights for predicting and analyzing deformation in similar projects.